Are Children Like Werewolves? Full Moon and Its Association with Sleep and Activity Behaviors in an International Sample of Children - Chaput, Jean-Philippe; Weippert, Madyson; LeBlanc, Allana G.; Hjorth, Mads F.; Michaelsen, Kim F.; Katzmarzyk, Peter T.; Tremblay, Mark S.; Barreira, Tiago V.; Broyles, Stephanie T.; Fogelholm, Mikael; Hu, Gang; Kuriyan, Rebecca; et al. (Frontiers in Pediatrics, 2016)
In order to verify if the full moon is associated with sleep and activity behaviors, we used a 12-country study providing 33710 24-hour accelerometer recordings of sleep and activity. The present observational, cross-sectional study included 5812 children ages 9-11 years from study sites that represented all inhabited continents and wide ranges of human development (Australia, Brazil, Canada, China, Colombia, Finland, India, Kenya, Portugal, South Africa, United Kingdom and United States). Three moon phases were used in this analysis: full moon (±4 days; reference), half moon (±5-9 days) and new moon (±10-14 days) from nearest full moon. Nocturnal sleep duration, moderate-to-vigorous physical activity (MVPA), light-intensity physical activity (LPA) and total sedentary time (SED) were monitored over 7 consecutive days using a waist-worn accelerometer worn 24 hours a day. Only sleep duration was found to significantly differ between moon phases (~5 min per night shorter during full moon compared to new moon). Differences in MVPA, LPA and SED between moon phases were negligible and non-significant (<2 min per day difference). There was no difference in the associations between study sites. In conclusion, sleep duration was 1% shorter at full moon compared to new moon while activity behaviors were not significantly associated with the lunar cycle in this global sample of children. Whether this seemingly minimal difference is clinically meaningful is questionable.